FACILITATING DIGITAL PROJECT-BASED LEARNING INTEGRATED WITH LOCAL WISDOM AND DEEP LEARNING IN ISLAMIC CULTURAL HISTORY EDUCATION AT DARUL QURAN SENIOR HIGH SCHOOL MOJOKERTO - Hajar Nurma wachidah; Amy Krisdiana (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2025)
The subject of Islamic Cultural History (SKI) is often considered to be textual memorization material, so there is a need for innovative learning media that is relevant to technological developments. This community service aims to provide assistance in creating local wisdom-based digital projects using a Deep Learning approach at Darul Quran High School in Mojokerto. The implementation method uses Participatory Action Research (PAR), which involves socialization, content development workshops, and technical assistance. The main focus of this project is the digitization of historical Islamic sites in Mojokerto using simple artificial intelligence technology for object classification and historical narration. The results of the community service showed an 85% increase in students' understanding of SKI material and a 78% increase in teachers' digital literacy skills. The integration of local wisdom in digital projects has proven to increase students' emotional attachment to Islamic history in their environment, while equipping them with future technology skills.